Transforming management using artificial intelligence techniques - Garg, Vikas; Agrawal, Rashmi, 1978- (Boca Raton : CRC Press, 2020)
"This book provides a deeper understanding of the relevant aspects of Artificial Intelligence impacting each others efficacy for better output. It's a reliable and accessible one-stop resource that introduces AI, presents a full examination of applications, provides an understanding of the foundations, examines education powered by AI, entertainment, home and service robots, healthcare re-imagined, predictive policing, space exploration and so much more, all within the realm of Artificial Intelligence"--
OCLC-licensed vendor bibliographic record.
Keywords: Management -- Technological innovations; Artificial intelligence; Organizational change; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Manufacturing